2021
DOI: 10.21037/jtd-20-2026
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review: how long should patients with cough variant asthma or non-asthmatic eosinophilic bronchitis be treated?

Akio Niimi

Abstract: The causes of chronic cough can be categorized into eosinophilic and noneosinophilic disorders, and approximately 30% to 50% of people with chronic cough have eosinophilic airway inflammation, the presence of which can be confirmed by sputum eosinophilia or elevated exhaled nitric-oxide levels. Cough variant asthma (CVA) is a phenotype of asthma which lacks wheezing or dyspnea, and consistently one of the most common causes of chronic cough worldwide. CVA and non-asthmatic eosinophilic bronchitis (NAEB) shares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…5A and C, Table S4). However, it was studied that the IL-17 signaling pathway was closely related to Th1 airway inflammation in asthma, while CVA was generally recognized as Th2 airway inflammation [45][46][47] . Therefore, we inferred that Suhuang may have other therapeutic effects on Th1 asthma (Fig.…”
Section: Identifying Cva-related Pathways Via Pathway Enrichment Anal...mentioning
confidence: 99%
“…5A and C, Table S4). However, it was studied that the IL-17 signaling pathway was closely related to Th1 airway inflammation in asthma, while CVA was generally recognized as Th2 airway inflammation [45][46][47] . Therefore, we inferred that Suhuang may have other therapeutic effects on Th1 asthma (Fig.…”
Section: Identifying Cva-related Pathways Via Pathway Enrichment Anal...mentioning
confidence: 99%
“…Patients with cough-variant asthma who do not use inhaled corticosteroids have a progression rate to classic asthma of 30%-40% (3). Several factors that influence the progression of cough-variant asthma to classic asthma include airway hyperresponsiveness, excessive airway response to methacholine, sputum eosinophilia and sensitisation to allergens (21). The early use of inhaled corticosteroid therapy can reduce the risk of progression to classic asthma (3).…”
Section: Management Of Cough-variant Asthmamentioning
confidence: 99%
“…Cough is a normal defense mechanism of the human body and many diseases like respiratory infections, airway inflammatory diseases, and pulmonary malignancy present with cough as a primary symptom ( 1 ). In particular, cough is the most distressing symptom in patients with asthma during an acute exacerbation, and it is also the only symptom in cough variant asthma ( 2 ). Cough may precede dyspnea or wheezing in an acute asthma exacerbation, and evidence has been found that monitoring nocturnal coughs may detect asthma exacerbations earlier ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%